1993
DOI: 10.1029/92wr02466
|View full text |Cite
|
Sign up to set email alerts
|

Kernel flood frequency estimators: Bandwidth selection and kernel choice

Abstract: Kernel density estimation methods have recently been introduced as viable and flexible alternativesto parametric methods for flood frequency estimation. Key properties of such estimators are reviewed in this paper. Attention is focused on the selection of the kernel function and the bandwidth. These are the parameters of the method. Existing techniques for kernel and bandwidth selection are applied to three situations: Gaussian data, skewed data (three-parameter gamma), and mixture data. The intent was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 42 publications
0
36
0
3
Order By: Relevance
“…Alila (1988) used data from two river basins and showed that this new method explicitly recognizes the characteristics of probability distributions of floods generated by more than one hydrological process, without the need for splitting the various populations. However, it has been argued that the non-parametric estimators have virtually no tail and may lead to unreliable quantile estimates beyond the largest observed value (Lall et al, 1993).…”
Section: Flood-frequency Analysis With Heterogeneous Distributionsmentioning
confidence: 99%
“…Alila (1988) used data from two river basins and showed that this new method explicitly recognizes the characteristics of probability distributions of floods generated by more than one hydrological process, without the need for splitting the various populations. However, it has been argued that the non-parametric estimators have virtually no tail and may lead to unreliable quantile estimates beyond the largest observed value (Lall et al, 1993).…”
Section: Flood-frequency Analysis With Heterogeneous Distributionsmentioning
confidence: 99%
“…Lall et al, 1993), which do not ®x a priori the form of the probability functions. Whatever the procedure adopted, though, the estimation of the exceedance probability is always based on the assumption of the stationarity of the hydrological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a nonparametric estimator is consistent, whereas a misspeci®ed parametric PDF has a bias that does not reduce with increasing sample size. This has led to the increased use of nonparametric methods in several areas of hydrology including frequency analysis of extreme events (Lall et al 1993) and hydrologic time series simulation (Sharma et al 1997;Tarboton et al 1997;Lall and Sharma 1996). Readers are referred to Lall (1995) for an overview of nonparametric applications in hydrology.…”
Section: Introductionmentioning
confidence: 99%